2018
DOI: 10.1103/physrevd.97.054514
|View full text |Cite
|
Sign up to set email alerts
|

QCD phase diagram for nonzero isospin-asymmetry

Abstract: The QCD phase diagram is studied in the presence of an isospin asymmetry using continuum extrapolated staggered quarks with physical masses. In particular, we investigate the phase boundary between the normal and the pion condensation phases and the chiral/deconfinement transition. The simulations are performed with a small explicit breaking parameter in order to avoid the accumulation of zero modes and thereby stabilize the algorithm. The limit of vanishing explicit breaking is obtained by means of an extrapo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
263
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(293 citation statements)
references
References 77 publications
27
263
3
Order By: Relevance
“…Similar conclusions were found in [23]. It is also worth noting that a recent study of QCD with nonzero isospin chemical potential [5] found a phase diagram very similar to that of [8], namely a pion condensed phase at low T and large µ, with a critical temperature that is nearly independent of µ, and a deconfinement transition line that intersects with the pion condensation transition.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar conclusions were found in [23]. It is also worth noting that a recent study of QCD with nonzero isospin chemical potential [5] found a phase diagram very similar to that of [8], namely a pion condensed phase at low T and large µ, with a critical temperature that is nearly independent of µ, and a deconfinement transition line that intersects with the pion condensation transition.…”
Section: Introductionsupporting
confidence: 79%
“…The apparent linear j-dependence at all µ may be an indication that non-analytic behaviour only sets in at lower j-values than we have here. To improve on the diquark source extrapolation, it may be necessary to carry out a reweighting procedure as outlined in [5], or explore much smaller values of the source ja [20]. At T = 90 MeV (N τ = 16) we see that qq is significantly smaller for all values of µ, suggesting that this temperature is near the critical temperature for the superfluid to normal phase transition.…”
Section: Results From Fine Ensemblementioning
confidence: 99%
See 1 more Smart Citation
“…Again there will be finite corrections to μ I ¼ 1 2 m π and in some cases, the deviation can be substantial [35]. Finally, we mention that the lattice result [13][14][15] for the onset of pion condensation at T ¼ 0 for 2 þ 1 dynamical quarks is in agreement with this. Likewise, their simulations strongly suggest that the transition is second order in the Oð2Þ universality class in agreement with expectations.…”
Section: A Homogeneous Chiral Condensatesupporting
confidence: 74%
“…Systems at zero baryon chemical potential and finite isospin chemical potential are of particular interest, since the fermion determinant is real and one can perform lattice simulations using standard importance sampling techniques, see e.g. [11][12][13][14][15]. The picture that emerges from the simulations is that at T ¼ 0, the chiral condensate is constant for μ I below a critical value, μ c I ¼ 1 2 m π .…”
Section: Introductionmentioning
confidence: 99%